PROFILE OF NURSES ON CLIMACTERIC WOMEN HEALTH CARE (Fiep Bulletin - online, 2014)
In time of transition between reprodutive fase and don´t reprodutive of woman,occur a physiological phenomenon resulted from the exhaustion ovarians follicles,followed of progressive fall estradiol secretion,culminating with definitive interruption of menstrual cicles and appear symptoms characteristics. This process represents climacteric stage. The nursing, through their role through the operation of the National Policy for Woman Health within the Family Health Strategy, it is shown as an important tool in the care of  climacteric woman. Basic atention it´s level appropriate for  answer the big part needs of woman health in this fase.This study aimed to characterize the profile of the nurse assisting the climacteric woman in primary care in the city of Cajazeiras-PB. This exploratory-descriptive study with a quantitative approach, as subjects had 14 nurses working in the health units from the city of Cajazeiras - PB. The informations was collected  through questionnaire semi-structured. It was found that the study subjects are predominantly female and are mostly aged 24 to 30 years. Regarding vocational training, most completed the course in the period 2001 to 2009. In all possess Post graduation.Considerable majority (93%) said it had conducted training focused attention to woman health climate, fact that compromises the effectiveness of care for non-reproductive period.Consequently,it´s necessary the implementation of  municipal public politics that promove  nursing  capacitation and sensibilization as woman atention in this  climateric stage
Keywords: Climacteric; Nursing; Family Health.